Comparação entre diferentes intercamadas contendo silício para adesão de filmes de DLC sobre substrato de aço AISI 4140 - Boeira, Carla Daniela (My University, 2017)
Diamond-like carbon (DLC) films research has a high academic appeal, is being developed for more than four decades. Nowadays, the industrial needs in their properties, such as high wear resistance and superlow friction coefficient, boosted the development of different applications in large scales and many fields [1]. However such applications are restricted by the low adhesion of this material on steel. An alternative for solving this problem is the deposition of a silicon-containing interlayer [2]. However, there are few methodical studies of dependence on key parameters such as temperature and process use of silicon-containing liquid precursors such as tetramethylsilane (TMS), hexamethyldisiloxane (HMDSO) and tetraethoxysilane (TEOS). In this work, different interlayer were deposited by using these three precursors on AISI 4140 steel substrates in order improve the DLC film adhesion. The treatments were done in bipolar pulsed-DC PECVD equipment with electrostatic confinement. The samples were characterizes in details by means of FEG-SEM, EDS, GD-OES and nanoscratch tests. On the one hand, FEG-SEM images revealed an interlayers thickness dependence on deposition temperature, which is quite similar in the all samples. On the other hand, EDS and GDOES analysis identified and quantified intensities variation of iron, silicon, hydrogen, oxygen and carbon intensities that are elements responsible for the structure DLC/interlayer/substrate. The GD-OES analyzes allowed to identify the variation of concentration the elements present in the interlayer for each precursor used. Corroborating these results, linear nanoscratch tests showed delamination to DLC in different loads, indicating the influence of concentration to elements on the adhesion of the film. The critical delamination load for DLC films deposited on interlayers deposited by HMDSO at 300 °C is greater than 500 mN (equipment limit). Finally, the critical load for TMS at 300 °C is 313.8 mN and for TEOS at 300°C is 306 mN, where the concentration of the oxygen and silicon elements present in the interlayer impaired adhesion of the DLC film. The interlayer deposited by the precursor HMDSO points to the greater amount of C, consequently the greater number of C–C bonds promotes better adhesion of the DLC film to a temperature of 300 °C.
Estudos de filmes de carbono tipo diamante (Diamond like-carbon – DLC), com elevado apelo acadêmico, são desenvolvidos a mais de quatro décadas. Entretanto, nos dias de hoje, o interesse industrial em suas propriedades, como alta resistência ao desgaste e ultra baixo coeficiente de atrito, impulsionou o desenvolvimento de diferentes aplicações em larga escala para diversas áreas. No entanto, essas aplicações são restritas pela baixa adesão deste material sobre ligas de aço. Uma alternativa para a solução deste problema é a deposição de uma camada intermédia contendo silício. Porém, existem poucos trabalhos metódicos da dependência de parâmetros-chave como a temperatura e tempo de processo no uso de precursores líquidos contendo silício tais como tetrametilsilano (TMS), hexametildissiloxano (HMDSO) e tetraetilortossilicato (TEOS). Neste trabalho, foram depositados diferentes intercamadas usando estes três diferentes precursores sobre substrato de aço AISI 4140, a fim de melhorar a adesão do filme DLC. Os tratamentos foram realizados em um equipamento tipo PECVD com confinamento electrostático e fonte bipolar DC pulsada. As amostras foram caracterizadas por meio de FEG-SEM, EDS, GD-OES, RAMAN e testes nanoscratch. As análises de FEG-SEM revelaram uma dependência na espessura da intercamada com a temperatura de deposição, semelhante em todas as amostras estudadas. As análises de EDS e GD-OES identificaram e quantificaram a variação de intensidades dos elementos que evidenciam a estrutura DLC/intercamada/substrato. As análises de GD-OES permitiram identificar a variação da concentração dos elementos presentes na intercamada para cada precursor utilizado. Corroborando com esses resultados, os testes de nanoesclerometria linear evidenciaram a delaminação do DLC em diferentes cargas, indicando a influência da concentração de elementos sobre a adesão do filme. A carga crítica de delaminação para filmes DLC depositados sobre intercamadas depositadas por HMDSO a 300 °C é superior a 500 mN (limite do equipamento). Finalmente, a carga crítica para o TMS a 300 °C é 313,8 mN e para TEOS a 300 °C é 306 mN, onde a concentração dos elementos oxigênio e silício presentes na intercamada prejudicaram a adesão do filme de DLC. A intercamada depositada pelo precursor HMDSO aponta para a maior quantidade de C, consequentemente o maior número de ligações C–C promove uma melhor adesão do filme de DLC à temperatura de 300 oC.
Keywords: Filmes finos de diamantes; Adesão; Carbono; Silício; Diamond thin films; Adhesion; Carbon; Silicon